Natural Regeneration Problem in Silver Fir (Abies pindrow) and Spruce (Picea smlthiana) Forests: Solutions Ahead - Singh, Ombir; Singh, V. R. R.; Rattan, Vidya (Indian Forester, 2011)
The allelopathic study on silver fir and spruce showed that leachates of humus have inhibitory effects on seed germination and on radicle and plumule growth; however, litter leachates have no such pronounced effect. Foliage leachates of Sarcocoocca saligna, Viburnum nervosum and ferns (understorey plants) have more inhibitory effects on seed germination and radicle growth. It seems that leachates of fern and Viburnum nervosum are mainly respousible for very less germination on forest floor as reported in fir and spruce forests. There is no self intoxicity on germination and early growth in silver fir and spruce. The research concludes that humus and foliage of specific plants are responsible for regeneration failure in these conifers and not litter as supposed till date.